2019
DOI: 10.1021/acs.jmedchem.9b00412
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging a Low-Affinity Diazaspiro Orthosteric Fragment to Reduce Dopamine D3 Receptor (D3R) Ligand Promiscuity across Highly Conserved Aminergic G-Protein-Coupled Receptors (GPCRs)

Abstract: Previously, we reported a 3-(2-methoxyphenyl)-9-(3-((4-methyl-5-phenyl-4H-1,2,4-triazol-3-yl)thio)propyl)-3,9-diazaspiro[5.5]undecane (1) compound with excellent dopamine D 3 receptor (D 3 R) affinity (D 3 R K i = 12.0 nM) and selectivity (D 2 R/D 3 R ratio = 905). Herein, we present derivatives of 1 with comparable D 3 R affinity (32, D 3 R K i = 3.2 nM, D 2 R/D 3 R ratio = 60) and selectivity (30, D 3 R K i = 21.0 nM, D 2 R/D 3 R ratio = 934).Fragmentation of 1 revealed orthosteric fragment 5a to express an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…To generate SAR, the new library of compounds was tested in radioligand binding assays at both human-cloned D 2 R (hD 2 R) and D 3 R (hD 3 R) receptor subtypes using agonist [ 3 H]-( R )-(+)-7-OH-DPAT and/or antagonist [ 3 H]- N -methylspiperone (Table ). We have found that the D 2 R active state agonist binding is significantly more sensitive ,,, to the radioligand used with respect to D 3 R. As a consequence, the use of [ 3 H]-( R )-(+)-7-OH-DPAT allows an accurate determination of apparent affinities for both targets, and selectivity, valuable to better correlate measured binding values with predicted and/or experimentally determined functional profiles, ,,, which would be otherwise dramatically overestimated in favor of the D 3 R when the antagonist [ 3 H]- N -methylspiperone is used [Table , comparison between D 3 R and D 2 R selectivity ratios between K i s obtained using [ 3 H]- N -methylspiperone or [ 3 H]-( R )-(+)-7-OH-DPAT].…”
Section: Results and Discussionmentioning
confidence: 99%
“…To generate SAR, the new library of compounds was tested in radioligand binding assays at both human-cloned D 2 R (hD 2 R) and D 3 R (hD 3 R) receptor subtypes using agonist [ 3 H]-( R )-(+)-7-OH-DPAT and/or antagonist [ 3 H]- N -methylspiperone (Table ). We have found that the D 2 R active state agonist binding is significantly more sensitive ,,, to the radioligand used with respect to D 3 R. As a consequence, the use of [ 3 H]-( R )-(+)-7-OH-DPAT allows an accurate determination of apparent affinities for both targets, and selectivity, valuable to better correlate measured binding values with predicted and/or experimentally determined functional profiles, ,,, which would be otherwise dramatically overestimated in favor of the D 3 R when the antagonist [ 3 H]- N -methylspiperone is used [Table , comparison between D 3 R and D 2 R selectivity ratios between K i s obtained using [ 3 H]- N -methylspiperone or [ 3 H]-( R )-(+)-7-OH-DPAT].…”
Section: Results and Discussionmentioning
confidence: 99%
“…The molecular docking studies were performed using the previously reported methods [21]. Fallypride, FTP, and KX-02-065 structures were drawn using the ChemDraw Professional 15.1 (PerkinElmer Informatics, Inc., Waltham, MA, USA).…”
Section: Molecular Dockingmentioning
confidence: 99%
“…The dataset of inactives ( SC60 – SC127 ) was also derived from the ChEMBL and comprised 68 compounds with a K I higher than 50 µM. The inactive dataset is shown in Table S2 [ 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. The decoy dataset including 3752 compounds was generated utilizing the DUD-E webtool ( [ 93 ], accessed on 15 March 2021) and based on the structures of the active dataset.…”
Section: Resultsmentioning
confidence: 99%